Հայ դասական կոմպոզիտորների երգերն ու ռոմանսները ԱՎԵՏԻՔ ԻՍԱՀԱԿՅԱՆԻ բանաստեղծություններով - Մոսեսի Արմենակյան Արմեն (Musical Armenia, 2010)
Analitical Review: Post-graduate of YSC after Komitas, singer Armen Mosesi Armeniakyan introduces the article “Armenain classical composers’ song’s and romances in Avetik Isahakyan’s poems”. The subject of this article is scientific-analytical study of a number of musical works by Armenian composers in poetic texts by A.Isahakyan.